Kindling change: shaping a New Fire Culture in Mediterranean socioenvironmental systems from the roots (Human Geographies – Journal of Studies and Research in Human Geography, 2024)
In line with global trends, the Valencian Region (Spain) is experiencing increasingly extreme wildfires, exacerbated by entangled socioenvironmental factors like climate change, the human-nature dichotomy, and wildfires managed basically through technocratic approaches. Rural grassroots movements are emerging amid worsening wildfires, advocating for local agency to build socioenvironmental resilience in wildfire-prone territories. Inspired by these movements, we propose a transformative paradigm – a New Fire Culture – to elicit critical reflections on current wildfire management and build socioenvironmental just futures. By drawing on our experiences around the 2022 Vall d'Ebo and 2023 Villanueva de Viver wildfire events and resulting from an interdisciplinary deliberation process, we present a comprehensive analysis of the present wildfire context and suggest guiding principles for a New Fire Culture. Acknowledging its context-specificity, we call for transdisciplinary processes among local actors, academics, and practitioners to collectively explore and build a New Fire Culture within their socioenvironmental systems.